Analysis of Speech Acts in the Movie Encanto: Focusing on Mirabel’s Identity - Tri Inda; Selviana Napitipulu (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the use of speech acts in the animated film Encanto (2021), with a particular focus on the main character, Mirabel Madrigal, and how her language reflects the construction of her identity. Using a qualitative descriptive approach, this research analyzes 43 utterances spoken by Mirabel based on J.L. Austin’s Speech Act Theory, which categorizes speech acts into locutionary, illocutionary, and perlocutionary acts. The findings reveal that illocutionary acts are the most dominant type, indicating that Mirabel frequently speaks with clear intentions such as expressing determination, questioning, persuading, and conveying emotions. This dominance highlights Mirabel’s role as an active communicator who uses language to negotiate her position within a family defined by magical power. Although locutionary and perlocutionary acts appear less frequently, they still play important roles in supporting narrative development and emotional impact. Overall, the study shows that language functions as Mirabel’s primary strength in expressing self-worth, challenging family expectations, and asserting her identity. Through her speech acts, Mirabel demonstrates that identity can be constructed not through magical abilities, but through words, intentions, and meaningful interaction.